Discovering childhood in contemporary China: Toward a multisystems perspective. Issue 2 (26th December 2022) - Ge, Ting; He, Guangye
Abstract: Despite the remarkable improvements that have been achieved in the field of child development in contemporary China, there remain daunting challenges. To explore and address these issues, we organize this special issue "Child development in contemporary China: Toward a multisystems perspective." In this collection, we introduce theoretically‐informed empirical research conducted by scholars worldwide and organize these research articles into four general themes: policy/program intervention regarding child development, migration status and child development, parenting/grandparenting and child development, and school/after‐school engagement and child development. These articles keep abreast of theoretical, methodological, and practical innovations in the field, aiming to provide new evidence to enrich the understanding of the patterns and potential mechanisms that would lead to a (dis)advantaged childhood in China.